Stimulating ion flow in oil palm leaves and midribs applying electrical potential difference - Toto Saktioto; Suhardi Suhardi; Defrianto Defrianto; Dewi Indriyani Roslim; Awitdrus Awitdrus (Kuwait Journal of Science)
Oil palms can live for >20 years. Crop yields are affected by fertilization (a chemical aspect), growth rate and evolution (agricultural aspects), and plant health and genetic features (biological aspects). Electrical treatment (a physical aspect) can be used to enhance growth. We applied direct currents to accelerate ion flow in oil palms. Trees aged 1–4 years were subjected to potentials of 10, 16, 25, 35, or 50V. Leaf and midrib geometries and ion levels were evaluated in an attempt to optimize oil palm productivity.